Research Progress in the Mechanism of Effect of PRP in Bone Deficiency Healing - Ning Zhang (The Scientific World Journal, 2013)
Platelet-rich plasma (PRP) therapy is a recently developed technique that uses a concentrated portion of autologous blood to try to improve and accelerate the healing of various tissues. There is a considerable interest in using these PRP products for the treatment used in bone deficiency healing. Because PRP products are safe and easy to prepare and administer, there has been increased attention toward using PRP in numerous clinical settings. The benefits of PRP therapy appear to be promising, and many investigators are exploring the ways in which this therapy can be used in the clinical setting. At present, the molecular mechanisms of bone defect repair studies have focused on three aspects of the inflammatory cytokines, growth factors and angiogenic factors. The role of PRP works mainly through these three aspects of bone repair. The purpose of this paper is to review the current evidence on the mechanism of the effect of PRP in bone deficiency healing.